Case Studies in Multiple Sclerosis - Giacomini, Paul S. (Springer International Publishing : Imprint: Adis, 2017)
This handbook is a collection of clinical narratives that underscore the heterogeneous and unpredictable presentation of multiple sclerosis (MS) and give real-world clinical context to recent drug developments. This accessible and concise publication is intended to be used by a wide range of medical professionals, from specialist neurologists to medical trainees with an interest in neurology. An ideal clinical resource, Case Studies in Multiple Sclerosis provides an evidence-based discussion of each case, with an aim to enhance effective diagnosis and treatment of patients with MS and MS-related conditions.
Keywords: Medicine.; Neuroradiology.; Neurology.; Primary care (Medicine).; elektronické knihy; electronic books